UiTM Sarawak expedition - Chan, Margaret (Universiti Teknologi MARA, Sarawak, 2004)
This article describes an expidition by Universiti Teknologi MARA (UiTM) Sarawak through Gunung Mulu National Park. The team travelled through forests and rivers, including crossing the Terikan River and trekking near Gunung Benarat. Despite rain and strong river currents, the group continued their journey with the help of experienced porters. Along the way, they learned the adventure before finally travelling by boat to Mulu National Park.